Effect of Intake and Long-acting Antipsychotics Drugs with Neuroleptic Malignant Syndrome - Jeikawati Jeikawati; Irvin Marcel; Suprihatini Suprihatini; Marihot Aruan (Indoscholar Publication and the Indonesian Psychiatric Association, 2023)
The use of antipsychotic therapy, both oral and injection, needs to pay attention to side effects, one of which is Malignant Neuroleptic Syndrome (SNM). A 50-year-old female patient was admitted due to decreased consciousness, with a history before the patient was brought to the ER, the patient was given a typical long-acting antipsychotic injection therapy by health workers at the local health care facility for 7 days. the patient does not want to eat/drink, and the patient is allowed to go home with oral medications Haloperidol 2x2,5 mg, Lorazepam 2x1 mg (after antipsychotic injection). Oral drugs have not been taken, the patient when he got home experienced a loss of consciousness. In the past 1 month ago, the patient experienced a change in symptoms, namely experiencing fear, such as being chased by people, the police. These changes have been experienced since the patient experienced a loss because the patient's husband died one year ago due to illness. The administration of oral antipsychotics or injections of typical long-acting needs to pay attention to the patient's intake and general condition of the patient by considering the side effects that can occur in the administration of typical antipsychotics, one of which is SNM.